Transgenic learning for STEAM subjects and virtual containers for OER - Burgos, Daniel; Corbi, Alberto (Distance Education, 2018)
Transgenic learning is a disruptive approach in education. It encourages modification of moving parts of the educational chain. This article provides a view of transgenic learning focused on the delivery of enriched learning contents in STEAM areas. It discusses the mutagenic role that the virtual containers may play in current distance education. We focus on the containers' technology and how it can bridge students, computing resources, teachers and specific IT needs. We also present an experiment carried out at UNIR University where we describe the transition from using conventional software distribution methods to the use of containers. Thanks to this virtualization approach, it is possible to deliver the necessary software-based lab scenarios. The results show that the participation and satisfaction of the students increased over time. Our experience shows that the combination of open educational resources, containers, and modern distribution channels can play a significant role in STEAM education.
Keywords: virtual containers; STEAM; open educational resources; content distribution platforms; JCR; Scopus